Review on High Temperature Heat Damage of Maize in China - Huo Zhiguo; Zhang Haiyan; Li Chunhui; Kong Rui; Jiang Mengyuan (应用气象学报, 2023)
As the climate warms, the threat of high temperature to China's maize production is increasing. Starting from the concept and classification of high temperature heat damage, the research progress is systematically summarized, expounding the hazard mechanism, meteorological causes, disaster causative indicators, spatial and temporal distribution and defense countermeasure of high temperature heat damage of maize, and the future research trend is also discussed. The high temperature heat damage of maize in China has a long duration, and its impacts can be divided into four categories:Delay, obstacle, poor growth and mixed. High temperature reduces the photosynthetic rate of maize, weakens pollen activity, inhibits the scattering of powder, shortens the filling time, and causes the yield and quality of maize to decrease. The high temperature and heat damage weather in maize growing areas is mainly caused by abnormal circulation and affected by the degree of atmospheric dryness. The meteorological causes, main types and occurrence periods of high temperature and heat damage are different in each dominant maize region. The disaster indicators include physiological and biochemical indicators and meteorological indicators, but there is no clear and unified standard for distinguishing high-temperature heat damage in maize at present. In the past 10 years, the intensity and frequency of heat damage of maize have increased. High temperature and heat damage of spring maize mostly occurs in flowering and pollination period, and the risk is higher in northeast Liaoning and southwest of Northeast China. High temperature heat damage of summer maize is more likely to occur after the jointing period, and is more frequent in southeastern Hebei Province, most of Henan Province and western Shandong Province. There are two methods to prevent the high-temperature heat damage of maize. The research on monitoring and early warning of high-temperature heat damage is still in its infancy, and the adverse effects of high-temperature heat damage on maize can be reduced by selecting appropriate field cultivation and management measures. The future research should focus on establishing a comprehensive dynamic maize high temperature heat damage index system, strengthening the simulation and risk assessment and further developing a refined monitoring and early warning service system.